Dynamics of Health Decisions in Elderly with Multimorbidity: Findings from a Qualitative Approach - Bangun, Argi Virgona; Nanda Sulistyani Putri, Syanita Dwi; Aminullah, Muthia Arfha (Jurnal Pendidikan Keperawatan Indonesia, 2024)
Introduction: Understanding health decision-making among elderly individuals with multimorbidity is essential for improving their care, especially in the context of polypharmacy. As the number of older adults with multiple chronic conditions increases, it becomes crucial to explore how they navigate complex healthcare choices that affect their well-being and quality of life. Objective: This qualitative study aimed to explore the decision-making processes of elderly individuals with multimorbidity undergoing polypharmacy. Method: Nine elderly individuals with multimorbidity from the Citeureup Cimahi Health Center were purposively sampled for in-depth interviews and field notes. Data were analyzed thematically using Colaizzi’s method. Result: The analysis identified five key themes: (1) decision-making dynamics, (2) navigating health opportunities, (3) adaptation and self-management, (4) support systems and communication, and (5) contextual influences. Conclusion: The study highlights the complex factors influencing health decisions among elderly individuals with multimorbidity, including aging, illness, financial barriers, and the need for more comprehensive healthcare. It underscores the importance of respecting autonomy and creating a healthcare system that prioritizes comfort, dignity, and quality of life.